The synthesis and characterization of a novel (E,E)-dioxime and its mononuclear complexes containing 1,3-dioxolane moieties - Canpolat, E; Kaya, M (Polish Chemical Soc, 2003)
A new ligand including vic-dioxime moiety, 9,10-bis(hydroxyimino)-4,8,11,15 -tetra-aza- 1,2,17,18-O-dialpha-methylbenzaloctadecane (LH2) has been synthesized and its mononuclear complexes have been prepared. LH2 forms transition metal complexes [(LH)(2)M] with a metal:ligand ratio of 1:2 with M = Co(II)(H2O)(2), Ni(II) and Cu(II). Zn(II) forms with H2L complex [Zn(LH2)(Cl)(2)], which has a metal:ligand ratio of 1: 1. The mononuclear Co(II), Ni(II), Cu(II) and Zn(II) complexes indicated that the metal ions are ligand coordinated through the two N atoms, as do most of the vic-dioximes. In the Co(II) complex two water molecules and in the Zn(II) complex two chloride ions are also coordinated to the metal ion. Elemental analyses, IR, H-1- and C-13-NMR spectra, UV-Visible spectroscopy, magnetic susceptibility measurements, conductivity measurements and thermogravimetric analyses (TGA) were used to elucidate the structures of the newly prepared ligand and its complexes. These results indicate octahedral geometry for the Co(II) complex, square planar geometry for the Ni(II) and Cu(II) complexes, tetrahedral geometry for the Zn(II) complex.
Keywords: vic-dioxime; transition metal complexes; cobalt; nickel; copper and zinc